Influence of Vegetation Structure and Canopy Cover on Litter Carbon Stock in Traditional Agroforestry Systems - Syarif Ohorella; Rima H Siburian; Ihsan Febriadi; Mira H Soekamto; Ris Hadi Purwanto; Zulkarnaen Sangadji (Universitas Pattimura, 2026)
Traditional agroforestry systems play a crucial role in maintaining ecosystem stability, enhancing the ecological functions of tropical landscapes, and supporting carbon cycling through the accumulation of biomass and litter. This study aimed to analyse the influence of vegetation structural attributes, including tree density, basal area, and canopy cover, on litter biomass and litter carbon stocks in traditional agroforestry systems in Southwest Papua, Indonesia. Data were collected from 30 systematically established sample plots measuring 20 × 20 m in Baingkete and Klayili Villages. Each plot was assessed through vegetation inventories, basal area measurements, canopy cover assessments, and litter sampling. Litter biomass was oven-dried and subsequently converted into carbon stock using the IPCC conversion factor of 0.47. The results showed that the mean litter biomass reached 0.886 kg m⁻², equivalent to 8.86 t ha⁻¹ of dry litter biomass, resulting in an estimated litter carbon stock of 4.28 t C ha⁻¹. Correlation and regression analyses revealed significant positive relationships between vegetation structural attributes and litter biomass. Basal area exhibited the strongest relationship with litter biomass (r = 0.79, R² = 0.62, p < 0.001), followed by tree density and canopy cover. These findings demonstrate that stand maturity and vegetation structural complexity are key determinants of litter production and associated carbon inputs. Therefore, the conservation of multistrata agroforestry systems is essential for enhancing carbon sequestration potential, supporting climate change mitigation efforts, and strengthening carbon accounting initiatives.